1997
DOI: 10.1021/np970231s
|View full text |Cite
|
Sign up to set email alerts
|

Mueggelone, a Novel Inhibitor of Fish Development from the Fresh Water Cyanobacterium Aphanizomenon flos-aquae

Abstract: A novel C18 lipid, containing a 10-membered lactone, mueggelone (1), was isolated from a field-collected sample of Aphanizomenon flos-aquae, together with the known compound lupenyl acetate (3). Both structures were secured using extensive spectroscopic analysis (1D and 2D NMR, MS, IR). Biological activity assessment of both compounds indicated them to have significant inhibitory effects on fish embryo larval development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 7 publications
0
38
0
Order By: Relevance
“…However, a limited number of investigations have similarly utilized the zebrafish embryo assay to investigate toxins from other cyanobacteria. Papendorf et al (1997), for example, demonstrated that mueggelone and lupenyl acetate isolated from Aphanizomenon flos-aquae were toxic to zebrafish embryos at 10 and 100 μg/ mL, respectively. Microcystin, on the other hand, was found to be toxic to zebrafish embryos at concentrations as low as 5 ng/mL; however, the observed effects only manifested as minor reductions in survival and body size of postdevelop-mental larvae but not during embryo development .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a limited number of investigations have similarly utilized the zebrafish embryo assay to investigate toxins from other cyanobacteria. Papendorf et al (1997), for example, demonstrated that mueggelone and lupenyl acetate isolated from Aphanizomenon flos-aquae were toxic to zebrafish embryos at 10 and 100 μg/ mL, respectively. Microcystin, on the other hand, was found to be toxic to zebrafish embryos at concentrations as low as 5 ng/mL; however, the observed effects only manifested as minor reductions in survival and body size of postdevelop-mental larvae but not during embryo development .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the zebrafish embryo model is being utilized extensively (e.g., Oberemm et al, 1997;Papendorf et al, 1997;Chang et al, 2004;Lefebvre et al, 2004;see Teraoka et al, 2003) to identify developmental toxicity of sublethal doses of naturally occurring toxins. However, in this case, although lower concentrations of the pahayokolide A produced lower numbers of dead embryos, no specific or consistent effect on embryo development, such as morphological malformation or apparent dysfunction of developmental processes, were observed.…”
Section: Discussionmentioning
confidence: 99%
“…5) With mueggelone at a concentration of 10 mg/ml, zebra fish larvae showed 45% mortality, and the surviving larvae showed edema in the heart region and thrombosis. This compound is thought to play an ecologically important role in inhibition of the development of herbivorous fish.…”
Section: Synthetic Approaches To Mueggelonementioning
confidence: 99%
“…Banwell's group (2004, entmicrocarpalide), 44) Chavan's group (2005), 45) and Fürst-ner's group (2007) 46) employed precursor 18 (or ent-18), the same intermediate as in Marco's synthesis. 22,23) Synthesis of ent-microcarpalide by Banwell and Loong is shown in Scheme 2 [5]. 44) They constructed the intermediate ent-18 by cross metathesis 4,19) of , -unsaturated ester 44 using 2nd-generation Grubbs catalyst 20) under ethylene, because direct methylenation of hemiacetal 43 (conversion to ent-18) was not successful, and RCM of , -unsaturated ester 44 did not proceed.…”
Section: Other Syntheses Of Microcarpalide Employing Rcmmentioning
confidence: 99%
See 1 more Smart Citation